Gas‐Phase 3D Printing: Gas‐Phase 3D Printing of Functional Materials (Adv. Mater. Technol. 12/2020). Issue 12 (9th December 2020) - de la Huerta, Cesar Arturo Masse; Nguyen, Viet H.; Sekkat, Abderrahime; Crivello, Chiara; Toldra‐Reig, Fidel; Veiga, Pedro Brandao; Quessada, Serge; Jimenez, Carmen; Muñoz‐Rojas, David
Abstract : In article 2000657, David Muñoz‐Rojas and co‐workers report the area‐selective deposition of functional materials using customized spatial atomic layer deposition (SALD) close‐proximity heads. Customized heads can be easily fabricated through 3D printing in different materials, including cheap resins, and allow the deposition of custom patterns, including multiple materials, without the need for substrate pre‐patterning or intermediate etching steps. Designing a miniaturized SALD head with concentric gas channels, i.e. a SALD pen, 3D printing of functional materials can be performed with nanometric resolution in Z.